KLASIFIKASI KATEGORI BUKU PADA PERPUSTAKAAN TEKNIK INFORMATIKA UNIVERSITAS ISLAM LAMONGAN - Nurul Qomariyah; Nur Nafi’iyah; Ayu Ismi Hanifah (Joutica, 2018)
The large number of library materials in the form of new book available in the library every year cause officer have difficulty in classification process book. Similarly, faced by librarian of Islamic University of Lamongan became the object of this research, determining the type or category of book at first the usual system. The process is made a lot of errors because it is based on the knowledge of officers from reading the title or the appropriate category so that makes it difficult for library users to find the materials needed. Application applied in the research is a data classification application that is done automatically using the application developed by Naive Bayes Classifier method with the application of client software web-based. Web-based server application function to input book by administrator and to classify data book based on the title. Based on the experience, and then in this research built an Classification Of Books Category At The Islamic University Of Lamongan Engineering Library